Theory and Spectroscopy of Nitrogen-Doped Vertically-Aligned Multi-Walled Carbon Nanotubes - Cortez Gómez, Sebastián Ismael (2019)
Carbon nanotubes (CNTs) are one of the most actively studied fields of research due to their outstanding mechanical, thermal, optical and electrical properties. The modification of the crystalline structure of CNTs by placing defects or foreign atoms in their hexagonal lattice is an effective method for tuning their electrical and mechanical properties. The addition of nitrogen, containing one additional electron as compared to carbon, has been shown to yield novel electrical and mechanical properties within CNTs. In recent years, there has been a great interest in vertically- aligned carbon nanotubes (v-CNTs) as both, a mean for inducing field emission and as a material for vacuum microelectronic devices. Growing carbon nanotubes over a large conducting surface is essential to obtain the uniform emission needed for vacuum nano-electronic devices. It is even more important to enhance the electronic properties of those v-CNTs by tuning their electronic properties via doping as shown in the case of N-doped CNTs. This project focuses on analyzing the grafting of nitrogen atoms via ion irradiation at the tips of vertically-aligned carbon nanotubes synthesized by catalytic chemical vapor deposition (CCVD). For the grafting we studied the dependence on acceleration voltages between 0.5 and 4.0 kV. We have performed a combined density functional theory (DFT) and x-ray photoelectron spectroscopy (XPS) study to systematically characterize the influence of N-doping on the local electronic and chemical structure of CNTs.